Notes on a Theology of the Word. The H. U. von Balthasar's Dialogue with K. Barth on the 'Analogia Entis' - Sueiro, Samuel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Analogy within the theological discourse is part of the capital themes of fundamental theology: the possibility of a real discourse about god’s mystery. Four writings of the theologian Hans Urs von Balthasar established a real dialogue with Karl Barth’s theology. Analyzing these writings we can extract conclusions about the characteristics proper to catholic recourse to analogy and theology’s foundations and purpose itself. Before being a simple linguistic tool, analogy is an ontological and transcendental question since it points to a concrete reality (revelation in existence) and leads to the trinitarian mystery of god in relation with the creation. Theology treats analogy with a double question for the philosopher and the theologian. For the philosopher because it situates itself in the relationship between the finite and the infinite, in other terms within the sphere of truth, or wisdom. For the theologian because of a two-fold reason: analogy is the form of god’s revelation through human language (words, actions and existence), and because the task of theology is in itself called to be philosophical and metaphysical in its search for the truth.
Keywords: Analogia entis; Balthasar; Barth; fundamental theology; theological discourse.